Antenatal Depression and Its Risk Factors Among Public Clinic Attendees: A Cross-Sectional Study in Urban and Rural Area of Limpopo, South Africa - Salane, Mulalo; Mokwena, Kebogile (Al-Sihah : The Public Health Science Journal, 2025)
Antenatal depression is a common yet underdiagnosed mental health issue with serious implications for maternal and child well-being. While its prevalence is well-documented globally, limited research exists on its burden and contributing factors within primary health care settings in rural South Africa. The purpose of this study was to screen for symptoms of antenatal depression and explore associated factors among clinic attendees in primary health care facilities in the Capricorn Health District, Limpopo Province, South Africa. The Edinburgh Postnatal Depression Scale-10 (EPDS-10) was used to screen for symptoms of antenatal depression, and a quantitative questionnaire was used to collect socio-demographic data. The ages of the sample ranged from 18 to 44 years, with a mean age of 28 years. The greatest proportion, 46% (n = 186), were single, and the majority were unemployed, 67% (n = 270), with 53.25% (n = 243) having completed high school. Almost half, 47.25% (n = 189), had not planned their pregnancy. The prevalence of antenatal depression symptoms was high, at 46% (n = 184). Factors associated with antenatal depression symptoms included being unemployed, having a previous diagnosis of postnatal depression (PND), dissatisfaction with the relationship with one’s partner, and lack of financial, social, and emotional support from the partner, as well as experiencing severe stress in the previous six weeks. The results highlight the need for routine antenatal screening for depression in primary health care facilities, where the majority of pregnant women access prenatal care.